PENGARUSUTAMAAN NILAI-NILAI MODERASI BERAGAMA BERBASIS PENGEMBANGAN MASYARAKAT - Hanafie, Imam; Zamroni, Zamroni (Atthiflah: Journal of Early Childhood Islamic Education, 2024)
The diversity of the Indonesian nation is the most beautiful gift from God. But Indonesia's diversity can one day turn into a disaster when the nation's children cannot take care of it, one way to take care of it is to continue to echo and ground the values of religious moderation. This research uses library research method and content analysis method. The results showed that (1) one way to take care of Indonesia is to continue to make efforts to realize the mainstreaming of religious moderation values into various aspects of the life of the nation and state. (2) The manifestation of the mainstreaming of religious moderation values must always be carried out simultaneously and synergistically between the government and society through various ways, namely continuing to promote through: Education and Counseling, Capacity Building and Training, Establishment of Interfaith Forums and Dialogues, Joint Social and Humanitarian Activities, Use of Media and Technology and Policies and Regulations